Pengaruh Kualitas Pelayanan Terhadap Kepuasan Masyarakat dalam Pelayanan Administrasi Kependudukan di Dinas Kependudukan dan Pencatatan Sipil, Padang Lawas Utara - Benni Kurniawan; Marlon Sihombing; Hatta Ridho (Universitas Medan Area, 2023)
Public service is one of the 8 (eight) areas of change in the Grand Design of Bureaucratic Reform 2010 - 2025, with the achievement target at the end of the reform period to improve the quality of public services. North Padang Lawas Regency is one of the new autonomous regions in North Sumatra Province. Some of the problems that become obstacles in meeting community satisfaction include: first, low adherence to Service Standards; second, lack of employee empathy in providing services; third, lack of information related to services; the fourth problem is the absence of a Community Satisfaction Survey. This study uses a quantitative method that is used to determine the effect between service quality variables (X) and community satisfaction (Y). The results showed that service quality had a positive and significant effect on community satisfaction.